Combined Assurance Strategy in Sharia Audit for Detecting Hifz al-Mal Violations in Islamic Financing - Umar, St Hafsah (Journal of Economic Education and Entrepreneurship Studies, 2025)
The growth trajectory of Indonesia’s Islamic banking sector continues to reflect a positive trend; however, the industry remains confronted with critical challenges related to sharia non-compliance, particularly within financing instruments such as murābaḥah, muḍārabah, mushārakah, and ijārah. Various forms of non-compliance have emerged at both administrative and substantive levels, indicating potential violations of the ḥifẓ al-māl principle within the framework of maqāṣid al-sharīʿah. This study aims to explore and conceptualize an effective sharia audit strategy to detect such irregularities by proposing a four-pillar auditing model that integrates: (1) fatwa- and PSAK-based checklist mechanisms, (2) a combined assurance approach between the Sharia Supervisory Board and internal audit units, (3) strengthened professional competence and auditor scepticism, and (4) risk-based audit mapping. Employing a descriptive qualitative design through systematic library research, the study synthesizes primary regulatory texts and recent empirical scholarship using thematic classification and content analysis. The findings indicate that sharia auditing practices which remain focused on administrative compliance are insufficient for identifying substantive deviations. Consequently, a risk-oriented, collaborative, and maqāṣid-driven audit framework is required to ensure the protection and preservation of transactional value. This research contributes to the development of an operational and value-based sharia audit model that can support internal policy implementation within Islamic financial institutions and serve as an academic foundation for enhancing national sharia auditing standards.